Pests and diseases as constraints in the production and marketing of fruits in the Caribbean - Brathwaite, Chelston W.D. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
In this document explain the seminar held in Barbados in 1985 sought to identify those pests and diseases which might act as constraints to the production and marketing of fruits in the region. En este documento se explica que el seminario realizado en Barbados en 1985 buscó identificar aquellas plagas y enfermedades que pudieran actuar como limitantes para la producción y comercialización de frutas en la región.